Agriculture Automation and Crop Monitoring using Android - Prabhu, L; Shankar, Pravin; Vanmathi, C; Mangayarkarasi, R (International Journal of Computer Sciences and Engineering, 2015)
The objective of the paper is to present a conceptual model of a micro controller based equipment which will monitor the crop. Analyzing the climatic data allows us to provide real-time information about the state of crop both in quality and quantity, with the possibility of early warning on alarm situations so that timely interventions can be planned and undertaken. In the proposed system we are using different sensors to monitor the temperature, humidity and irrigation process. Temperature sensor is used in monitoring the crop’s soil temperature and humidity sensor, monitoring humidity level of soil. So we are integrating all the major factors that influence crop yielding to get a better overall monitoring capability to reduce manual labor involved in agriculture. This simply increases the cost effectiveness, water efficiency, convenience and the ability for the farmers to be absent from fields occasionally. If any abnormality is found, irrigation process will stop automatically.